PENERAPAN SISTEM INFORMASI MANAJEMEN PADA PENGAMBILAN KEPUTUSAN DI DEPARTEMEN SDM - Firstianty Wahyuhening Fibriany (CAKRAWALA: JURNAL HUMANIORA BINA SARANA INFORMATIKA, 2016)
Information systems smanagement (SIM) is used by all organizations, both government organizations as well as private organizations. One of the functions of the SIM is desperately wicked decision making and their impact on management in organizations. This approach is described with an emphasis on decision-making is structured as well as unstructured by each level of management level. Limitations and challenges in the field of HR SIM discussed and provide recommendations to improve the effectiveness of the SIM in the decision-making process in the Department of Human Resource Management. Keywords : Information System management, decision making, human resources management